Análise das respostas cardiovasculares de mulheres praticantes de treinamento funcional de alta intensidade - Freitas, Vanessa Alves (2024)
The study aims to evaluate the influence of training time on cardiovascular responses (blood pressure, heart rate and double product) of women undergoing a high-intensity functional training session of the CrossFit® modality. The sample consisted of 20 healthy women (31.2 ± 4.7 years) divided into 2 groups: beginners (n=10) and advanced (n=10) with a maximum of 12 months of practice in the modality. They underwent a high-intensity functional training session and had their cardiovascular variables monitored before training, immediately after and during the 60-minute period after the end of training, with a 10-minute interval between each measurement (10’, 20’, 30’, 40’, 50’ and 60’). The result of the study shows a greater variation in systolic and mean blood pressure, heart rate and double product in both groups. However, there was a faster recovery, after the intervention, to the baseline values of the variables in the advanced group. These variations, when compared with the initial data, pre-training in a resting state, were much more evident after 10 minutes of measurements at the time of recovery after exercise, in both groups. When comparing the groups, there were differences in systolic blood pressure, heart rate and double product, with a significant difference between the training time and the cardiovascular responses. The advanced group had a greater increase in SBP after acute intervention than the beginner group and later, during recovery, had a more significant decrease in SBP and HR and maintenance of these values for a longer period compared to the beginner group.